4x-9+2x=-6x+5-3

Simple and best practice solution for 4x-9+2x=-6x+5-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9+2x=-6x+5-3 equation:


Simplifying
4x + -9 + 2x = -6x + 5 + -3

Reorder the terms:
-9 + 4x + 2x = -6x + 5 + -3

Combine like terms: 4x + 2x = 6x
-9 + 6x = -6x + 5 + -3

Reorder the terms:
-9 + 6x = 5 + -3 + -6x

Combine like terms: 5 + -3 = 2
-9 + 6x = 2 + -6x

Solving
-9 + 6x = 2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-9 + 6x + 6x = 2 + -6x + 6x

Combine like terms: 6x + 6x = 12x
-9 + 12x = 2 + -6x + 6x

Combine like terms: -6x + 6x = 0
-9 + 12x = 2 + 0
-9 + 12x = 2

Add '9' to each side of the equation.
-9 + 9 + 12x = 2 + 9

Combine like terms: -9 + 9 = 0
0 + 12x = 2 + 9
12x = 2 + 9

Combine like terms: 2 + 9 = 11
12x = 11

Divide each side by '12'.
x = 0.9166666667

Simplifying
x = 0.9166666667

See similar equations:

| 3*4+14-5-[-2]*7=-23 | | x+54=y | | -3k-1=12 | | x=3y(y+w)-1 | | k=5/8m | | 4x-9+2x=-6x+5 | | 6(3x+2)+5(7x-6)-12x=6(x-3)+5(6x-1) | | X^2-8x=100 | | 7xy+2y^2=1 | | 20y^4+35y^3+15y^2= | | 78-u=271 | | -1(t^2-3t-10)=0 | | -1=5-2x/3 | | x-23=x+77 | | -98/-18 | | (-8-90)/2(-8)-2 | | (-8-90)/2x(-8)-2 | | 4m^2-36mn+81n^2= | | x+4.9=6.89 | | 2.6x-52=1.3x | | 2.6x-52=1.3 | | 5x-27=x+30 | | 8ab^2-12a^2b= | | 2(y+x)=-(-3x+10) | | 29-35=-5 | | 8x-20=2x+40 | | 4x-7=-x-9 | | a^2+11=3a | | x^2+y^2+16x-12y+10=0 | | x^2+20x-74=8x-10 | | 3x^2-5-4x=10x+65-3x | | 6x+1=-0.4x-2 |

Equations solver categories